Catch Composition of Demersal Fish Using Millennium Gillnet Fishing Gear in Tambak Lorok Semarang - Mutiara Khansa Ramadhani; Ahmad Naufal Attaqi; Bagus Aris Wibowo (PT. Gyandharma Global Media, 2025)
The Millennium Gillnet is a passive fishing device whose operation takes advantage of dark and light time conditions. This study was conducted to find out the type and composition of the catch of millennium gillnet operated in Tambak Lorok, Semarang City. The method was used in this study is a survey. The implementation of the research was carried out from October 31 to November 28, 2024. The data taken were in the form of primary data and secondary. The results showed that 10 types of millennium gillnet obtained, namely Baracuda (Sphyraena barracuda), Senangin (Eleutheronema tetradactylum), White snapper (Lates calcarifer), Kedukang (Hexanematichthys sagor), Sembilang (Plotosus canius), Red snapper (Lutjanus argentimaculatus), Laosan (Eleutheronema tetradactylum), Tigawaja (Johnius dussumieri), Lundu (Macrones gulio H.), Grouper (Epinephelus malabaricus). Percentage of catch composition in order: 7.69%; 5.76%; 59.61%; 1.92%; 9.61%; 5.76%; 1.92%; 1.92%; 3.84%. The study was concluded that 10 types of fish catches were obtained, with the composition of the most catch being white snapper (Lates calcarifer).